First-line treatment of chronic lymphocytic leukemia with ibrutinib plus obinutuzumab versus chlorambucil plus obinutuzumab: final analysis of the randomized, phase III iLLUMINATE trial - Moreno, Carol; Greil, Richard; Demirkan, Fatih; Tedeschi, Alessandra; Anz, Bertrand; Larratt, Loree; Simkovic, Martin; Novak, Jan; Strugov, Vladimir; Gill, Devinder; Gribben, John G.; Kwei, Kevin; et al. (Haematologica (Roma), 2022)
iLLUMINATE is a randomized, open-label phase III study of ibrutinib plus obinutuzumab (n=113) versus chlorambucil plus obinutuzumab (n=116) as first-line therapy for patients with chronic lymphocytic leukemia or small lymphocytic lymphoma. Eligible patients were aged ≥65 years, or <65 years with coexisting conditions. Patients received oral ibrutinib 420 mg once daily until disease progression or unacceptable toxicity or six cycles of oral chlorambucil, each in combination with six cycles of intravenous obinutuzumab. After a median follow-up of 45 months (range, 0.2-52), median progression-free survival continued to be significantly longer in the ibrutinib plus obinutuzumab arm than in the chlorambucil plus obinutuzumab arm (median not reached versus 22 months; hazard ratio=0.25; 95% confidence interval: 0.16-0.39; P<0.0001). The best overall rate of undetectable minimal residual disease (<0.01% by flow cytometry) remained higher with ibrutinib plus obinutuzumab (38%) than with chlorambucil plus obinutuzumab (25%). With a median treatment duration of 42 months, 13 months longer than the primary analysis, no new safety signals were identified for ibrutinib. As is typical for ibrutinib-based regimens, common grade ≥3 adverse events were most prevalent in the first 6 months of ibrutinib plus obinutuzumab treatment and generally decreased over time, except for hypertension. In this final analysis with up to 52 months of follow-up (median 45 months), ibrutinib plus obinutuzumab showed sustained clinical benefit, in terms of progression- free survival, in first-line treatment of chronic lymphocytic leukemia, including in patients with high-risk features. ClinicalTrials.gov identifier: NCT02264574.